Synthesis of 2-Fluoroacetoacetic Acid and 4-Fluoro-3-hydroxybutyric Acid - Mattingly, Stephanie J.; Wuest, Frank; Schirrmacher, Ralf (Synthesis, 2019)
The butyric acid scaffold is the base structure of several human metabolites that serve diverse and prominent biochemical roles including as oxidative sources of cellular energy and as substrates for biosynthesis. Derivatization of metabolites through incorporation of fluorine often alters bioactivity and can facilitate detection and analysis by nuclear magnetic resonance or positron emission tomography depending upon the fluorine isotope employed. We describe the synthesis of two new fluorinated butyric acids (and three related esters) that are derivatives of the metabolites acetoacetic acid and 3-hydroxybutyric acid. 4-Fluoro-3-hydroxybutyric acid is prepared from epoxy ester precursors via ring opening by triethylamine trihydrofluoride. 2-Fluoroacetoacetic acid is prepared by electrophilic fluorination of an acid-labile β-keto ester. The gradual pH-dependent decarboxylation of 2-fluoroacetoacetic acid is investigated by 19F NMR spectroscopy.
Keywords: fluorination; ketone bodies; acetoacetate; acetoacetic acid; 3-oxobutanoic acid; 3-hydroxybutanoic acid; β-hydroxybutyrate